CPhill

avatar
Имя пользователяCPhill
Гол130409
Membership
Stats
Вопросов 56
ответы 43413

 #1
avatar+130409 
+1

\(\frac{rs}{t^2} + \frac{rt}{s^2} + \frac{st}{r^2} \)

 

Simplify as

 

rs (rs)^2  + rt (rt)^2  + st (st)^2

________________________       =

            (rst)^2

 

 

(rs)^3  + (rt)^3   +  (st)^3

_____________________

           (rst)^2

 

By Viete

r + s + t =  4

(rs + rt + st)  = -7

(rst)  =  -12

 

And

(rs + rt + st)^3  =  (-7)^3 = -343 

 

( rs + rt + st)^3 =

[ (rs)^3 + (rt)^3  + (st)^3 ]  +   3rst [ r^2s + r^2t] + 3rst [ s^2r + s^2t] + 3rst [ t^2r + t^2s] + 6(rst)^2  = 

[ (rs)^3 + (rt)^3 + (st)^3 ]  +   3(-12) [ r ( rs + rt)] + 3(-12) [ s (rs + st)] + 3(-12) [ t(rt + st] + 6(-12)^2  =

[ (rs)^3 + (rt)^3 + (st)^3 ]  -  36 [ r(rs + rt) + s(rs + st)  + t(rt + st) ] + 864

 

Note: [ rs + rt + st] = -7

So 

rs + rt = -7 - st

rs + st  = -7 - rt

rt + st =  -7 - rs

 

So

 [(rs)^3 + (rt)^3 + (st)^3 ] -  36 ( r [ -7 - st]  + s [-7 - rt] + t [ -7 -rs] )  + 864  =   -343

 

[ (rs)^3 + (rt)^3 + (st)^3 ]  - 36 ( -7 [ r + s + t ] - 3 (rst) ]  =   -1207

 

[ (rs)^3 + (rt)^3 + (st)^3 ]  - 36 [ -7(4) - 3(-12) ]  =  -1207

 

[ (rs)^3 + (rt)^3 + (st)^3 ] - 36 [ -28 + 36 ]  =  -1207

 

[ (rs)^3 + (rt)^3 + (st)^3 ]  - 36(8)   =-1207

 

[ (rs)^3 + (rt)^3 + (st)^3] =  - 288 = -1207

 

[ (rs)^3 + (rt)^3 + (st)^3]  = -919

 

So

 

rs       +     rt      +     st

__           ___          ___  =

r^2           s^2          r^2

 

 

[ rs (rs)^2  + rt(rt)^2 + st(st)^2]

________________________   =

       (rst)^2

 

[ (rs)^3 + (rt)^3 + (st)^3]

___________________  =

       (rst)^2

 

 

-919 

____

 144

 

 

cool cool cool

24 февр. 2025 г.